2012
DOI: 10.1051/0004-6361/201219880
|View full text |Cite
|
Sign up to set email alerts
|

GOODS-Herschel: radio-excess signature of hidden AGN activity in distant star-forming galaxies

Abstract: Context. A tight correlation exists between far-infrared and radio emission for star-forming galaxies (SFGs), which seems to hold out to high redshifts (z ≈ 2). Any excess of radio emission over that expected from star formation processes is most likely produced by an active galactic nucleus (AGN), often hidden by large amounts of dust and gas. Identifying these radio-excess sources will allow us to study a population of AGN unbiased by obscuration and thus find some of the most obscured, Compton-thick AGN, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 147 publications
7
113
0
Order By: Relevance
“…In the absence of a more evolved selection method, we resigned ourselves to a brute force power density cut, where any source with a rest-frame log(P ν,1.4 GHz ) > 23.8 was considered an AGN. This is consistent with maximal radio output of normal galaxies (Condon 1992;Kauffmann et al 2008;Del Moro et al 2013) and consistent with the selection used by other studies (e.g., Hickox et al 2009) including other studies of SPIREselected galaxies (Hardcastle et al 2012).…”
Section: Active Galactic Nuclei Selection and Classificationsupporting
confidence: 91%
See 2 more Smart Citations
“…In the absence of a more evolved selection method, we resigned ourselves to a brute force power density cut, where any source with a rest-frame log(P ν,1.4 GHz ) > 23.8 was considered an AGN. This is consistent with maximal radio output of normal galaxies (Condon 1992;Kauffmann et al 2008;Del Moro et al 2013) and consistent with the selection used by other studies (e.g., Hickox et al 2009) including other studies of SPIREselected galaxies (Hardcastle et al 2012).…”
Section: Active Galactic Nuclei Selection and Classificationsupporting
confidence: 91%
“…Conversely, for sources significantly detected in the radio but with 23 < log(P ν,1.4 GHz ) < 23.8, such an excess is not observed in ∼90% of the sample. In addition, if we instead select radio AGN hosts by a radio-excess criteria using the methodologies of Del Moro et al (2013) none of the main results of this paper are substantially changed. Because of these reasons and because the q TIR measurements of individual sources are considerably less precise than log(P ν,1.4 GHz ) measurements and, furthermore, because adopting a cut based on the former limits both internal comparisons and comparisons to the literature which can be made without fear of differential bias, we choose to retain the definition of radio AGN hosts as those galaxies fulfilling the criterion log(P ν,1.4 GHz ) > 23.8.…”
Section: Active Galactic Nuclei Selection and Classificationmentioning
confidence: 95%
See 1 more Smart Citation
“…In particular, Del Moro et al (2013) showed that a simple cut at q100 < 1.5 (where q100 = log(S100µm/S1.4GHz)) selects ∼ 80 percent of the radio-excess sources defined using the total FIR. Following Del Moro et al (2013) we use q100 < 1.5 to identify radio-excess sources in our radio selected sample. Clearly, such a criterion is simplistic and does not take into account the z dependence, such that it may suffer of contamination, especially at high redshift, by strong IR sources (i.e.…”
Section: Radio-excess Sourcesmentioning
confidence: 99%
“…Many Spitzer Space Telescope and Herschel Space Observatory observations have been dedicated to detect the dust emission in galaxies up to z∼2 (e.g. Del Moro et al 2013). However, these studies are affected by the poor angular resolution (from few arcsec to ∼ 30 arcsec) of IR telescopes which cannot resolve compact structures at high redshift and are confusion limited.…”
mentioning
confidence: 99%